An Overview Of The Knowledge Of Married Women Of Childbearing Age About Cervical Cancer In Neighborhood II, Kelurahan Peace Stabat - Tri Suci Dewi Wati; Sri Gunana Br. Ginting (Science Midwifery, 2020)
Cervical cancer is a malignant process that occurs in the cervix / cervix so that the surrounding tissue cannot carry out its function as it should. According to the World Health Organization (WHO) 490 thousand women were diagnosed with cancer, 240 thousand of them died, 80% of these cases occurred in developing countries. Research objective: to determine the knowledge description of married women of reproductive age about cervical cancer in the environment II sub-district of peace, sub-district of stabat, Langkat district in 2013. Research methodology: This type of research is a descriptive survey using primary data. The population in this study were married women of childbearing age in the neighborhood II of Peace Village with a sample of 40 people. The results obtained that the majority of 40 respondents lacked knowledge as many as 22 respondents (55%), based on age >35 years as many as 24 (60.0%) based on high school education as many as 24 respondents (60%) with sufficient knowledge, based on occupation the majority of IRT were 28 (70%), based on sources of information from health workers as many as 18 (45%). Suggestions It is hoped that the community will be more active in seeking information related to women's health maintenance.